Total Physical Response (TPR) Method in Improving English Vocabulary Acquisition of 5-6 Years Old Children - Mariyam, Siti Nurfalah; Musfiroh, Tadkiroatun (Universitas Islam Negeri Raden Intan Lampung, 2019)
Nowadays, English has become one of the subjects that must be mastered. Thus, English learning should be done from an early age. This research aimed to describe how Total Physical Response (TPR) method can improve English vocabulary achievement in 5-6 years old children. TPR is the language learning approach which stimulates the children in acquiring their mother language which implemented in teaching foreign languages. The samples of this research were 5-6 years students of TK (Kindergarten) An-Nisa, Rokan Hilir, Riau Province, Indonesia with the total samples 15 students. This research used qualitative research. The data was analyzed by using descriptive statistics, analyzing the scores of English vocabularies. The results showed that noun categories had the highest percentage in vocabulary acquisition (97.78 %), then followed by verbs (86.67 %) and adjectives (62.22 %). Meanwhile, the percentages of vocabularies that used by children were verbs (24.44 %), nouns (11.11 %), while the children were still not capable in using adjectives (0 %). The results of this research is expected to contribute to the development of English learning for young learners.